2018
DOI: 10.2174/1381612824666180924141407
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Endogenous PACAP in Inflammation-induced Retinal Degeneration

Abstract: Purpose. Pituitary adenylate cyclase activating polypeptide (PACAP) is a neuroprotective peptide that has been shown to exert protective effects in different models of neurodegenerative diseases, including retinal degenerations. Data obtained from PACAPdeficient (PACAP KO) mice provide evidence that endogenous PACAP has neuroprotective role in different pathologies. PACAP KO mice show enhanced sensitivity to different insults, such as oxidative stress, hypoxia and inflammation. The aim of the present study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 95 publications
(119 reference statements)
4
23
0
Order By: Relevance
“…Degradation of PACAP1-38 in Systane ® Ultra at RT and +4°C (e). Higher stability was found at +4°C, similar to the other examined media kainate-and glutamate-induced excitotoxicity (Atlasz et al 2009;Seki et al 2006), UV light-induced lesion (Atlasz et al 2011), lipopolysaccharide-induced inflammation (Vaczy et al 2018), oxygen-induced retinopathy of prematurity (Kvarik et al 2016), diabetic retinopathy (D'Amico et al 2017;Szabadfi et al 2016) and high intraocular pressureinduced retinopathy (Seki et al 2011).…”
Section: Discussionsupporting
confidence: 74%
“…Degradation of PACAP1-38 in Systane ® Ultra at RT and +4°C (e). Higher stability was found at +4°C, similar to the other examined media kainate-and glutamate-induced excitotoxicity (Atlasz et al 2009;Seki et al 2006), UV light-induced lesion (Atlasz et al 2011), lipopolysaccharide-induced inflammation (Vaczy et al 2018), oxygen-induced retinopathy of prematurity (Kvarik et al 2016), diabetic retinopathy (D'Amico et al 2017;Szabadfi et al 2016) and high intraocular pressureinduced retinopathy (Seki et al 2011).…”
Section: Discussionsupporting
confidence: 74%
“…PACAP has also been shown to modify amyloid aggregation (Reglodi et al, 2018c) and has important preventive functions in aging (Reglodi et al, 2018a;Szegeczki et al, 2019). The general protective role of the neuropeptide has been demonstrated in various disorders, such as retinopathy (Vaczy et al, 2018), diabetes (Banki et al, 2014), Parkinson's disease (Reglodi et al, 2006;Reglodi et al, 2017), and inflammatory processes (Sakamoto et al, 2015). It has been shown that PACAP diminishes the harmful effects of oxidative stress (Juhasz et al, 2014a), ischemic conditions (Reglodi et al, 2018d), and mechanical overload (Juhasz et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…This process involves the loss of inner and outer hair cells in the inner ear 51 . It is also known that aging processes are accelerated in PACAP KO mice affecting several organ systems 14,25,3941 . An acceptable hypothesis could be that the changes we found in the auditory system of the PACAP KO mice are the result of the accelerated aging of the inner ear and auditory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…retinoblasts and cells of the olfactory system, indicating that PACAP has important functions in different sensory organs 10,11 . It has well-known retinoprotective effects in different lesions of the retina, which were described morphologically, functionally and at the molecular level 1214 . PACAP exerts protective functions in the olfactory system 15 .…”
Section: Introductionmentioning
confidence: 99%